1985
DOI: 10.1038/314377a0
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression of a foreign β-globin gene in erythroid cells of transgenic mice

Abstract: The globin gene family represents an attractive system for the study of gene regulation during mammalian development, as its expression is subject to both tissue-specific and temporal regulation. While many aspects of globin gene structure and expression have been described extensively, relatively little is known about the cis-acting DNA sequences involved in the developmental regulation of globin gene expression. To begin to experimentally define these regulatory sequences, we have taken the approach of intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
99
2
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(104 citation statements)
references
References 29 publications
2
99
2
1
Order By: Relevance
“…Surprisingly, all 5' deletion clones still maintained an appropriate up-regulation as the cells differentiated into myofibers except when combined with pBR322 sequences, which drastically inhibit transcription. The nature of this inhibitory effect is unknown, but it has been observed in a number of transgenic mouse experiments (5,53). One possibility for the inhibition of expression is that the high G+C content of plasmid sequences may produce structural alterations that inhibit interactions of the promoter with regulatory factors on RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, all 5' deletion clones still maintained an appropriate up-regulation as the cells differentiated into myofibers except when combined with pBR322 sequences, which drastically inhibit transcription. The nature of this inhibitory effect is unknown, but it has been observed in a number of transgenic mouse experiments (5,53). One possibility for the inhibition of expression is that the high G+C content of plasmid sequences may produce structural alterations that inhibit interactions of the promoter with regulatory factors on RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the LCR is an absolute requirement for the high level expression of the genes in the cluster [2,3]. The linkage of a human ]3-globin transgene to the LCR results in high level, erythroid specific expression in mice [4], in sharp contrast to constructs lacking LCR sequences which show a low, variable expression level [5][6][7][8]. The most characteristic feature of the LCR is its ability to override position effects when it is stably integrated into chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LaFlamme et al (27) transfected chimeric globin genes involving the exchange of the IVS2 between the human ,B-and b-globin genes into MEL cells and demonstrated that the IVS2 of human ,B-globin is necessary, but not sufficient, for inducible expression of the gene in MEL cells. In transgenic mice, the human ,B-globin gene is regulated as a mouse adult globin gene and expressed in both fetal and adult stages (9,29,48) and the human -y-globin gene is regulated as an embryonic globin gene (8). Chimeric lyl$-globin genes (joined at the BamHI site at the 3' end of exon 2) in transgenic mice are expressed as both embryonic and adult ,-globin genes (26), further implicating sequences downstream of exon 2 in the regulation of the ,B-globin gene.…”
mentioning
confidence: 99%